Pengaruh Media Permainan Dadu Putaran Karya Cipta terhadap Kemampuan Motorik Halus Anak Usia 5-6 Tahun di Tk Negeri Pembina Kecamatan Kota Barat Kota Gorontalo - Mianti Abdullah; Yenti Juniarti; Sulastya Ningsih (Inovasi Pendidikan dan Anak Usia Dini, 2025)
This research aims to determine whether dice games have an impact on the fine motor skills of children aged 5-6 years. This type of research is quantitative with an experimental research method. The research design used is a one-group pretest-posttest with data collection techniques including observation and tests. The subjects of this research are children aged 5-6 years with a sample size of 15 children. Based on the results of the t-test analysis (paired sample t-test), it was found that t count is greater than t table, that is 17.427 > 2.160 and sig. (2-tailed) = 0.000 < 0.05, so Ha is accepted and HO is rejected. It can be concluded that there is an influence of the designed dice game media on children's fine motor skills and an increase in fine motor skills in early childhood.